Bleeding Control of Dental Extraction in Patients Treated with Heparin Therapy (Journal of Pharmaceutical Negative Results, 2022)
Background: The administration of antiplatelet drugs to patients as part of heparin therapy is one method that can be used to prevent thrombosis. This can be done either prophylactically or in patients who are undergoing percutaneous coronary intervention. The purpose of this study was to investigate whether or not removing teeth prior to treatment with dual antiplatelet medication is effective. Materials and methods: There were a total of 200 people who were investigated for having dental extractions done on them. The epinephrine fraction and the adenosine fraction of collagen with the operative surface, as well as the post-surgical measures and the adverse consequences, were both evaluated. Following the completion of the surgical procedure, all of the patients were given tranexamic acid-impregnated gauzes and alveolar sutures as part of their post-operative care. For the purpose of making comparisons between quantitative variables, the student's t-test and the Pearson correlation coefficient were utilized. As a consequence of these comparisons, descriptive statistics were computed and examined. We considered a value of P that was less than 0.05 to be statistically significant. Results: Both the epinephrine fraction, which was measured at 441 ±22.3 seconds with a range of 13050 to 350 seconds, and the adenosine fraction, which was measured at 201± 12.23 seconds with a range of 130-350 seconds, were measured to be longer than the typical range. The results of this study show that both of these fractions are longer than the typical range. Because we took all of the necessary precautions after the surgery, not a single patient experienced any post-operative complications like bleeding, hematoma, or infection. Conclusion: It was possible to safely perform dental extractions on patients who were receiving dual antiaggregant therapy by making use of non-resorbable sutures and gauze that had been impregnated with tranexamic acid. The patient was instructed to hold the gauze in place for twenty minutes.